Microvascular decompression is effective method for treatment of trigeminal neuralgia in elderly patients - Borut Prestor (Zdravniški Vestnik, 2007)
Background: The study aimed to determine the possible differences in the effectiveness of microvascular decompression for the treatment of trigeminal neuralgia between patients aged 65 or younger and patients older than 65 years, and to clarify the efficacy and safety of the MVD in elderly patients. Methods: In 40 patients MVD was used for treatment of typical TN. The pain relief immediately and 2 years after MVD for TN in 22 patients aged more than 65 years and in 18 patients younger than 65 years was evaluated and compared between the groups. Other parameters were also compared, such as duration of pain before surgery, operative fitness status, type of vessel (artery or vein) compressing the nerve, length of hospital stay, and complications after the surgery. Results: There was no significant difference in immediate pain relief and pain relief 2 years after MVD between the older and younger patients (P = 0.381, P = 0.185). 2 years after MVD, more pain free patients were found in cases of arterial compression in both groups (P < 0.001). The patients in the younger group showed better operative fitness status (P = 0.027). Length of hospital stay was shorter in younger patients (P < 0.001). There were no fatal outcomes, cranial nerve deficits, or any other permanent neurological deficits in either of the groups. Conclusions: Microvascular decompression is a safe and effective treatment for typical trigeminal neuralgia in elderly patients. This surgical technique is more successful in cases of trigeminal nerve compression by an artery. Physical fitness and not patient age should be a limiting factor for microvascular decompression as the treatment of choice for trigeminal neuralgia.